Influence of Mg content on defect-related luminescence of undoped and doped wurtzite MgZnO ceramics - Markevich, I.V.; Stara, T.R.; Bondarenko, V.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Undoped as well as Li-, Ag-, Cu- and Zn-doped MgxZn₁₋xO ceramics with x = 0–0.20 were sintered at 1000 °C. Defect-related photoluminescence (PL) and PL excitation spectra were measured at room temperature in 400–800 nm and 250–400 nm spectral ranges, accordingly. Two types of PL bands were observed: i) the bands, spectral positions of which were not influenced by the Mg content (Cu-related as well as selfactivated orange and red ones); ii) the bands, spectral positions of which exhibited some blueshift with increasing Mg content (Li- and Ag-related and self-activated green ones). It has been shown that used doping gives the possibility to obtain the phosphor with intense visible emission within the blue-yellow spectral range.